Publishing Peaks: Mountaineering Literature and Italian Publishing in the 2000s (Altre Modernità, 2025)
In recent decades, fiction dedicated to mountaineering exploits – autobiographies and biographies – has earned a prominent position in the literary landscape. The typical elements of this ‘genre’, such as adventure, the wild and heroism, which have determined its publishing fortunes many times in the past, still prove capable of attracting readers today, but this is compounded by the effects of typically contemporary phenomena such as the growth of ecological demands that mountaineering narratives effectively manage to intercept. Taking these and other factors into consideration, the paper focuses on analysing the formal and thematic characteristics of the genre in order to identify the elements that attract the public and the reasons for its publishing success in Italy, with a particular look at the most successful volumes. An indicative overview is then presented of the constant expansion of the editorial space reserved for it, with an offer that unfolds in different formats, from e-books to audiobooks, and includes initiatives that indicate a sure success on the market, such as the inclusion of the biography of Gary Hemming – a cult figure in the world of climbing – among the podcasts adapted from successful books that Mondadori has recently launched in order to strengthen its presence in the sector.
Keywords: mountaineering; mountains; autobiography; genre literature; environmentalism